Pathogenic: Light or Dark Skin?. Issue 5 (7th April 2014) - den, Johan T.
ABSTRACT Currently, we use the term "pathogenicity" to indicate whether a variant in a gene has an influence on the phenotype or not. As this term is confusing, not neutral, and incorrectly refers to a disease state, it seems better to use a more neutral term. The suggestion is to use "affects function."